REHABILITASI BERSUMBERDAYA MASYARAKAT BAGI PENYANDANG DIFABEL DI SANGGAR INKLUSI MUTIARA BUNDA - Budi Kristiawan; Agung Tri Wijayanta; Suminah Suminah (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2016)
Sanggar Mutiara Bunda was a community-based rehabilitation for the disabled children to conduct the activities such as therapy and other social events for maximizing the ability of disabled children like Cerebral Palsy (CP), speech therapy for impaired speech disabilities and down syndrome treatment. In these activities, Sanggar Mutiara Bunda also used the concept of parenting in which every parent and family were involved in training and equipped with the knowledge and ability to perform activities of therapies and activities so that they can carry our themselves at home. By working with the health center that provide physicians and other medical personnel checked regularly the disabled children health. This place also carried out the counseling to motivate more advanced and independent. Design dedication to the empowerment of the disabilities included: 1) provides assistance to parents of children with disabilities to perform activities that are helping the family economy, 2) provide psychological counseling for parents of the disabled children, 3) complete the facilities and infrastructure needed in the treatment of children with disabilities.Keywords: Society-based rehabilitation, the disabled, training, counseling